Strategic Complementarity, Stabilization Policy and the Optimal Degree of Publicity - Jonathan James (Journal of Money, Credit and Banking, 2012)
This paper examines the welfare implications of public information dissemination within a model in which information is heterogeneous across agents and where a strategic complementarity is present. The focus of the analysis is on how the presence of stabilization policy affects the case for transparency. In considering this issue, it extends James and Lawler's (2011) contribution by incorporating an alternative payoff function and by employing a different representation of public disclosure. The study’s key finding is that the conclusions drawn in its precursor are robust to these modifications: specifically, in the presence of optimally-designed policy intervention zero transparency maximizes welfare.